Influence of Transformational Leadership Style and Principals’ Decision Making on High-School Teachers’ Organisational Commitment in Jakarta Laboratory Schools - Emmanuel Chinedu Elele (International Journal of Pedagogy and Teacher Education, 2020)
Laboratory schools are faced with the challenges of improving the quality of educational service delivery stemming from their role of being a platform for enhancing the school management skills of prospective teachers, and the demonstration of new teaching techniques towards the acceleration of student learning. The complex processes of determining and implementing school management policies is carried out by school management personnel, teachers and stakeholders. In this direction, organisational commitment, most significantly that of the teacher, is paramount to how effective laboratory schools can achieve their vision, mission and objectives. This quantitative study examines the pattern of relationships and the influence of the transformational leadership style and principals’ decision making on high school teachers’ organisational commitment at Jakarta laboratory schools. Research data was obtained by randomly administering questionnaires to a sample of eighty-nine (89) teachers. Data analysis was performed using descriptive and inferential statistics to provide detailed insight on the spread of research data and to facilitate the drawing of conclusions. The path analysis technique was used to determine the levels of influence between the transformational leadership style, the principals’ decision making and the teachers’ organisational commitment. Results from this study show that: (1) the transformational leadership style has a direct positive influence on high-school teachers’ organisational commitment at Jakarta laboratory schools; (2) the principals’ decision making has a direct positive influence on high-school teachers’ organisational commitment at Jakarta laboratory schools; and (3) the transformational leadership style has a direct positive influence on the principals’ decision making at Jakarta laboratory schools.